The Evolution of the Types of Public Procurement Contracts in Romania - Ionel PREDA; Doina I. POPESCU; Cezar-Petre SIMION (Communications of International Proceedings, 2020)
Given the very large sums being spent in public procurement systems, it is very important to analyse the distribution of procurement contracts by types (products, services and works) as it may reveal a number of deficiencies in terms of value, evolution and distribution by destination (consumption or investment) in various economic periods. The article describes the significant particularities of public procurement of services, products and works, the differences between them, analyses the use of public procurement of works (investment) as a factor for accelerating the economic recovery in case of the 2009-2010 economic crisis and studies the evolution of the types of public procurement contracts awarded in Romania between 2007 and 2017. Also, an estimate of the value of the contracts of works attributed by simple exponential smoothing method is developed in the article, the result of the estimation being compared with the actual data.
Keywords: Public Procurement; Procurement Procedure; Contract; Framework Contract; Works; Outsourcing.